Performance Assessment of Pregnant Ewes Fed Broiler Litter as Feed Supplement - Ososanya, T.O.; Odedire, J.A.; Oyeyemi, M.O. (Pakistan Journal of Nutrition, 2007)
Four low cost feed samples were formulated using 0, 25, 50 and 75% levels of broiler litter processed into feed along with other feed ingredients. All the animals were dewormed using Ivermectin and dipped against ticks and fleas using diazintol. Estrus was artificially synchronized in all the animals using Prostaglandin 2F-alpha, the animals were mated with rams of known fertility and lineage bred. They were evaluated in a pregnancy and pre-weaning growth trial. All the ewes were weighed before pregnancy and bi-monthly thereafter until parturition. The parameters studied were weights before and after parturition, weight gain in pregnancy, weight changes in lactation and nursing, lambs birth weights and daily weight of lambs, dam`s weight at weaning and gestation length. It was observed that weight at mating, weight before mating, weight at parturition, gestation length, weight gain in pregnancy, weight change in lactation and nursing, lambs birth weights and daily weight gain of lambs were significantly affected (p0.05). Results of this study indicate that inclusion of broiler litter up to 50% in feed mixtures of ewes has no deleterious effect on the performance and health status of ewes during pregnancy and lactation.